¿Locuciones verbales o locuciones adverbiales? - García-Page, Mario (Studia Romanica Posnaniensia, 2004)
There are fixed expressions which are difficult to classify in one of the categories because of their blurred edges, and their register in dictionaries and manuals is not uniform. This is the case of the sequences a cántaros and a dienteperro, which are sometimes described as adverbial idioms and on other occasions as an integral part of the verbal idioms llover a cántaros and coser a dienteperro (so-called complex collocations).